Skin conditions in early Parkinson's disease. (March 2021) - Dinesh, Deepika; Lee, Jong Soo; Gao, Xiang; Palacios, Natalia
Abstract: Objective: Skin conditions have been associated with increased risk of Parkinson's disease (PD). Little is known about clinical and biomarker differences according to presence of skin conditions among PD patients. Studying these differences might provide insight into PD pathogenesis. Methods: We examined the association between common skin conditions and risk of PD in a case-control study of 423 early drug-naïve PD cases and 196 healthy controls (HC) in the Parkinson's Progression Markers Initiative (PPMI). Among PD participants, we examined if skin conditions were associated with clinical and PD-relevant biomarkers. Results: Skin conditions occurred more frequently among PD participants (41%) relative to HC (32%). In multivariate analyses, we observed an association between any skin condition and PD (OR = 1.49, 95% CI = 1.03–2.16) and basal cell carcinoma and PD (OR = 2.05, 95% CI = 1.02–4.08). PD participants who reported skin conditions were older (OR = 1.68, 95% CI = 1.21–2.35) more educated (OR = 1.70, 95% CI = 0.99–2.91), had higher Semantic Fluency Test (SFT) scores (OR = 1.45, 95% CI = 1.07–1.96) and Hopkins Verbal Learning Test (HVLT) retention scores (OR = 1.55, 95% CI = 1.09–2.22) compared to PD patients without skin conditions. None of the associations remained significant after Bonferroni correction for multiple comparisons. Conclusions: We observed a positive association between any skin condition as well as basal cell carcinoma and PD. PD participants with skin conditions were older, more educated, had higher SFT and HVLT retention scores compared to those without skin conditions. However, all associations were no longer significant after Bonferroni multiple comparisons correction. Observed associations should be confirmed in larger, longitudinal studies. Highlights: We observed a positive association between skin conditions and Parkinson's Disease (PD) and basal cell carcinoma and PD. SFT total scores and HVLT retention scores were positively associated with presence of skin conditions in PD participants. None of the associations were robust after correction for multiple comparisons. Larger, longitudinal studies are needed to confirm the observed associations.